2010
DOI: 10.2353/ajpath.2010.091105
|View full text |Cite
|
Sign up to set email alerts
|

Vascular-Leukocyte Interactions

Abstract: Transformation of uterine spiral arteries is critical for healthy human pregnancy. We recently proposed a role for maternal leukocytes in decidual spiral artery remodeling and suggested that matrix metalloprotease (MMP) activity contributed to the destruction of the arterial wall. In the current study we used our first trimester placental-decidual co-culture (PDC) model to define the temporal relationship and test the mechanistic aspects of this process. PDC experiments were assessed by image analysis over a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 42 publications
0
69
0
Order By: Relevance
“…It must be noted that we did not formally establish that decidual macrophages have the capacity to migrate within our cultures; however, others have observed decidual macrophage migration in similar first-trimester organ cocultures of decidua and placental villi (48). Furthermore, the impairments in macrophage migration within decidual tissue are in line with previous work by Redline and colleagues, who demonstrated that macrophages do not localize near infectious foci in the deciduas of artificially decidualized and pregnant mice (6,23,28).…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that we did not formally establish that decidual macrophages have the capacity to migrate within our cultures; however, others have observed decidual macrophage migration in similar first-trimester organ cocultures of decidua and placental villi (48). Furthermore, the impairments in macrophage migration within decidual tissue are in line with previous work by Redline and colleagues, who demonstrated that macrophages do not localize near infectious foci in the deciduas of artificially decidualized and pregnant mice (6,23,28).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages and dNK cells can also produce many MMPs, such as MMP7 and -9 (Smith et al 2009), which along with pro-and anti-angiogenic factors such as VEGF, PGF and angiopoietins could influence vessel stability. Recent studies using placentaldecidual co-culture model have implicated MMP2 and -9 in the remodelling events initiated by leukocytes (Hazan et al 2010). Studies have indicated that dNK cells begin to disperse after spiral artery remodelling is complete, and are found in much reduced numbers at term (Williams et al 2009b).…”
Section: Factors Involved In Spiral Artery Remodellingmentioning
confidence: 99%
“…In humans, loss of vascular smooth muscle cells is accompanied by the influx of EVTs to envelope the arteries. These vessel-associated EVTs deposit extracellular matrix called fibrinoid that stabilizes the dilated, R94 M T Rätsep and others venous-like vessels (Smith et al 2009, Hazan et al 2010, Cerdeira & Karumanchi 2012, Robson et al 2012, Wallace et al 2012. The dogma currently held is that modified SAs are no longer under maternal vasomotor control.…”
Section: Roles Of Nk Cells In Physiological Changes To Maternal Samentioning
confidence: 99%